The End of the North-South Wage Differential: Comment - Ladenson, Mark L. (American Economic Review, 1973)
In a recent issue of this Review, Philip Coelho and Moheb Ghali have argued that various studies purporting to show a persistent differential between wages in northern and states have used data unadjusted for regional differences in price level; that the differential has been proved for nominal wages, not real wages. Using data for 1963 they show that the average nominal wage rate for a sample of five northern metropolitan areas is significantly greater than such an average for five southern metropolitan areas. However, after the nominal wage figures are adjusted for differences in the cost of living in each of the ten areas, this differential disappears. This result survives the introduction of dummy variables to account for differences in industry composition, sex, color, and capital-labor ratio. It seems almost unbelievable that earlier studies of the wage differential have ignored regional differences in price levels, and Coelho and Ghali must be commended for calling attention to this anomaly. However, they have not proved the end of the NorthSouth wage differential; at least not to the satisfaction of this writer. The reason is that of the five cities used in their sample, only one, Atlanta, would be accepted by many as southern, the classification of Baltimore, Dallas, Houston, and Washington, D.C. as by the Departments of Labor and Commerce notwithstanding.' The purpose of this note is to repeat Coelho and Ghali's comparisons for another sample of cities, half of whose members would be recognized as by any reasonable observer.2 Required data for each metropolitan area are number of production workers, total man-hours, and total wages for production workers, classified by industry, and cost of living indices. The first three items are provided in the Census of Manufactures 1967 and the latter can be obtained for the year 1967 from the Handbook of Labor Statistics 1970. Table 1 shows that our sample seems to give roughly the same results as that of Coelho and Ghali. Average hourly nominal wages for the five northern areas are 14.4 percent higher than for the areas. This differential drops to 4 percent when real hourly wages are considered. The same phenomenon occurs for annual wages. Looking at the figures for the individual cities however, it is clear that Baton Rouge is an extreme outlier. If we compare average hourly wages between the five northern areas and the four areas excluding Baton Rouge, we find that when we shift from nominal to real wages the percentage difference drops from 25.6 to 15.1, still a sizeable difference. It would be preferable to establish the continued existence of the North-South wage differential without excluding Baton Rouge from the sample. This might be accomplished by showing that the high average wages in Baton Rouge are a result of the industrial composition of that region. Our method of distinguishing between regional effects and industry effects is identical to that of Coelho and Ghali. We calculate wage rates and annual wages for every industry (two digit classification) and for every metropolitan area.3 The model takes the form: * Assistant professor of economics, Michigan State University. I The title of one of the sessions at the December 1971 meeting of the American Economic Association, at which two papers were presented, was Is the South Still Backward? M. I. Foster included only Atlanta in his definition of the South. F. Ray Marshall omitted Baltimore and Washington, D.C. from his definition. 2 We do not repeat the last part of their analysis involving regional differences in sex, color, and capitallabor ratio. 3 No observations were available for the following industries in: Boston, SIC 21; Buffalo, SIC 21, 31; Pitts-